External strengthening of unreinforced masonry walls with polymers reinforced with carbon fiber - Vega, Camilo; Torres, Nancy (Universidad Nacional de Colombia, 2018)
In many countries, buildings are usually made of unreinforced clay masonry walls, especially in Colombia. These constructions have low resistance and ductility, and are very vulnerable to seismic events, due to their low capacity of energy dissipation. This paper reports the results obtained from a research project that evaluates the behavior of reinforced masonry walls under lateral loads. The reinforcement was made using Carbon Fiber Reinforced Polymers (CFRP). In the test program, eight (8) clay masonry walls were built using hollow brick. Four (4) of them were 1,23 m long and 1,90 m high and the remaining four (4) were 2,47 m long and 1,90 m high. Four (4) walls were tested with a static lateral load and four (4) with a cyclic lateral load in its plane. Results revealed that the presence of the reinforcement material significantly increased the ultimate load and deformation capacity, provided that the material has a suitable anchoring system.

La construcción de viviendas con muros de mampostería en arcilla no reforzada es tradicional en muchos países, en especial en Colombia. Debido a su baja resistencia y ductilidad, estas edificaciones son muy vulnerables a eventos sísmicos como consecuencia de su poca capacidad de disipación de energía, lo que genera fallas que llevan incluso al colapso total. Este artículo expone los resultados de un proyecto de investigación donde se evaluó el comportamiento ante cargas laterales en muros de mampostería no estructural, reforzados mediante polímeros reforzados con fibra de carbono (CFRP). En el programa experimental, se construyeron ocho (8) muros de mampostería de arcilla, utilizando bloque de perforación horizontal. Cuatro (4) de ellos tenían dimensiones de 1,23 m de largo por 1,90 m de alto y los cuatro (4) restantes de 2,47 m de largo por 1,90 m de alto. Cuatro (4) muros se probaron ante carga lateral estática y cuatro (4) ante carga lateral cíclica en su plano. Los resultados muestran que el material de refuerzo mejoró significativamente la capacidad de carga y deformación última de los muros, siempre y cuando se tenga un adecuado sistema de anclaje.
Reforzamiento externo de muros de mampostería no reforzada mediante polímeros reforzados con fibra de carbono
Keywords: Mampostería; Masonry; Muros; Walls; Polímeros; Polymers; Resistencia de materiales; Strength of materials; Unreinforced masonry; Fiber reinforced polymers; Seismic retrofitting; Lateral loads; Mampostería no reforzada; Polímeros reforzados con fibra; Reforzamiento sísmico; Cargas laterales